The Principal's Strategy for Improving the Professional Competence of Teachers at Muhammadiyah Sinar Fajar Cawas Middle School for the 2024/2025 Academic Year - Astuti, Widhi; Khuriyah, Khuriyah (CV. Rayyan Dwi Bharata, 2025)
This study aims to determine: (1) to describe the principal's strategy in improving teachers' professional competence at Muhammadiyah Sinar Fajar Middle School, Cawas (2) to describe the factors that hinder the principal's efforts in improving teachers' professional competence at Muhammadiyah Sinar Fajar Middle School, Cawas. This research uses qualitative research methods. The research was conducted at SMP Muhammadiyah Sinar Fajar Cawas from August 28 to October 30, 2024. The subject of this research is the school principal. The informants of this research are the vice principal and the PAI teacher. Data collection techniques were carried out through observation, interviews, and document analysis. Meanwhile, the data document analysis technique used by the researcher is qualitative descriptive. The research results show that: (1) the principal's strategy in improving the professional competence of teachers at SMP Muhammadiyah Sinar Fajar Cawas Klaten is carried out through several means, including the principal's role in enhancing the professional competence of teachers. Some strategies implemented by the principal include mentoring, coaching, and motivation aimed at effectively achieving the desired professional goals of the teachers. Additionally, the impact of developing the professional competence of teachers at SMP Muhammadiyah Sinar Fajar Cawas Klaten includes several key factors, such as good communication between the principal and teachers, teacher awareness, teacher commitment, and shared goals. (2) Supporting factors include effective communication, the principal providing facilities for teachers and offering motivation, while the hindering factors are the high workload of teachers, not all teachers having the same motivation to attend seminars, teaching methods, and limited funding.